ANALISIS ISI KONTEN MEDIA SOSIAL INSTAGRAM @DELICUTE_ID DALAM MENINGKATKAN ENGAGEMENT - Aditiyo Nugroho; Intan Leliana; Laurensia Retno Hariatiningsih (An Nafi': Multidisciplinary Science, 2025)
This research aims to describe how the communication patterns of content on the Instagram account @delicute_id build engagement with followers. This research employs a qualitative method with a case study approach, using content analysis theories from Klaus Krippendorff and Denis McQuail. These methods and theories are applied to understand the visual message elements that attract follower interaction. The research data were obtained through observation, interviews, documentation, and relevant literature studies, providing a more comprehensive overview. The analysis focuses on Feed, Story, and Reels content, which serve different communication functions in delivering information, entertainment, and education. The findings indicate that Instagram is not only used as a promotional tool but also as a space for emotional interaction with the majority of Delicute’s followers, who are primarily young women and young mothers. This study shows that creative content communication patterns, appealing visuals, and structured presentation can establish strong relationships between the brand and its audience, thereby significantly enhancing engagement on this social media platform.